Everything chocolate : a decadent collection of morning pastries, nostalgic sweets, and showstopping desserts (America's Test Kitchen, 2020)
Chocolate may be the most universally loved (and craved) flavoring, and Everything Chocolate is the definitive guide to any sweet treat you can imagine featuring it, for any time of day. Wake up with streusel-topped Chocolate-Walnut Muffins that are easy to make or professional-grade Chocolate Croissants when weekend time allows. Pack lunches with pleasing Milk Chocolate Revel Bars or serve Magic Chocolate Flan Cake or Chocolate Pavlova with Berries and Whipped Cream after dinner. Much of why we fall for chocolate is because it brings back memories of candy bar snacks and sneaking just-baked chocolate chip cookies while they're still warm (we have the best recipe). We channel the nostalgia in recipes like Chocolate Fluff Cookies and Frozen Snickers Ice Cream Cake. But chocolate is also a grown-up favorite for black-tie desserts--think low, lush slices like Blood Orange Chocolate Tart or ganache-enrobed Chocolate-Pecan Torte (we'll teach you how to get a perfectly smooth coating). The full range of chocolate recipes is here, avoiding the pitfalls of unbalanced chocolate flavor (too bitter or too sweet) or dry, crumbly baked goods (chocolate contains starch and we've learned how to mind it). Become a home chocolatier by learning all about chocolate nomenclature, how to shop for the best-tasting cocoa powder, when you should use chocolate bars versus chips, decorating dazzling desserts with chocolate, and how to make candies and cookies with shiny, snappy chocolate coatings with our shortcut to tempering.--